Adolescents' Self-Perception and School Satisfaction: Assessing the Mediating Role of Subjective Vitality - Satici, Seydi Ahmet; Deniz, M. Engin (TURKISH EDUCATION ASSOC, 2019)
The purpose of this study was to examine whether subjective vitality is a mediator between self-perception and school satisfaction among adolescents. Totally 351 (176 girls and 175 boys, mean age = 13.87 +/- 1.57) adolescents completed a self-report questionnaire including the Children's Overall Satisfaction with Schooling Scale, the Subjective Vitality Scale, and the Social Comparison Scale. The data were analyzed with using the structural equation modeling and bootstrapping method. Structural equation modeling showed that self-perception had an indirect effect on school satisfaction, fully mediated by subjective vitality. The results of the bootstrapping procedure indicated that the indirect effect of subjective vitality on the relationship between self-perception and school satisfaction was significant. The possible explanations, the research implication, limitations, and future directions are discussed.
Keywords: Self-perception; Subjective vitality; School satisfaction; Adolescence; Structural equation modelling; Bootstrapping; SOCIAL SUPPORT; ACADEMIC-ACHIEVEMENT; COLLEGE-STUDENTS; HEALTH-BEHAVIOR; WELL; PERFORMANCE; LONELINESS; COMPETENCE; VALIDATION; PREDICTORS; Education & Educational Research